Как решить уравнение 3:(6-х у меня СОЧ​

dfgdfh2 dfgdfh2    3   27.10.2020 06:48    1

Ответы
Shersher8630166 Shersher8630166  26.11.2020 06:49

Пошаговое объяснение:

3:(6-х)+12=27

3:(6-х) = 27 - 12

3:(6-x) = 15

6-x = 3 : 15

6 - x = 0,2

x = 6 - 0,2

x = 5,8

ПОКАЗАТЬ ОТВЕТЫ
KristinkaOvchin KristinkaOvchin  26.11.2020 06:49

3:(6-х)+12=27

3:(6-x)+12=27 , x ≠6

\frac{3}{6-x} +12=27

\frac{3}{6-x} =27-12

\frac{3}{6-x} =15

3=15(6-x)

3=90-15x

15x=90-3

15x=87

x=\frac{29}{5} , x ≠6

x=\frac{29}{5}=5\frac{4}{5} =5,8

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика